45° FLEXION ANTEROPOSTERIOR ELBOW RADIOGRAPHS IMPROVE DIAGNOSTIC ACCURACY OF CAPITELLUM OSTEOCHONDRITIS DISSECANS. Issue 7 (30th July 2021) - Saper, Michael; Burton, Monique; Menashe, Sarah; Nagle, Kyle; Schmale, Gregory; Bompadre, Viviana; Thapa, Mahesh
Background: The initial diagnosis of capitellum osteochondritis dissecans (OCD) is typically confirmed using standard anteroposterior (AP) and lateral elbow radiographs, despite low sensitivity, which is approximately 44-47%. An AP image of the elbow in 45° of flexion has been suggested to increase diagnostic accuracy. Purpose: To assess the diagnostic performance, inter- and intra-observer reliability, and confidence level for identifying capitellum OCD using plain radiographs (AP, lateral, and 45° flexion AP) in pediatric and adolescent patients. Methods: This was a retrospective study including pediatric and adolescent patients with capitellum OCD and a healthy control group. Independent clinicians were blinded to the official radiologists' reports and reviewed images on a picture archiving and communication system on two separate occasions 1 week apart. A 5-point Likert scale was used to assess the clinicians' level of confidence (1-not at all confident; 5-very confident). Inter- and intraobserver reliability was determined using kappa statistics. Results: The study included 28 elbows (24 patients) with a mean age of 12.5 ± 2.0 years. 64.3% were female. There were no differences in age ( P = 0.18), sex ( P = 0.62), or laterality ( P = 1.0) between the two groups. There were marked variations in the sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy for each of the following views: AP: Sensitivity 85.1; Specificity 89.3; PPV 88.8; NPV 85.7; accuracy 87.2. Lateral: Sensitivity 73.2; Specificity 91.7; PPV 89.8; NPV 77.4; accuracy 82.4. 45° flexion AP: Sensitivity 91.7; Specificity 91.1; PPV 91.1; NPV 91.6; accuracy 91.4. Standard radiographs (AP and lateral views) failed to diagnose capitellum OCD in 4.8% of cases. The sensitivity of the three combined views was 100%. Confidence levels in the clinicians' diagnostic assessments were similar for each view (AP, 4.0; lateral, 4.0; and 45° flexion AP, 4.1). Interobserver reliability was substantial for AP and lateral views (k=0.65 and k=0.60, respectively) but highest for the 45° flexion AP radiographs (k=0.72). Intraobserver reliability for all views was moderate to perfect (k=0.52 to 0.93). Conclusion: The 45° flexion AP view can detect capitellum OCD with excellent accuracy, a high level of confidence, and substantial interobserver agreement. When added to standard AP and lateral radiographs, capitellum OCD can be diagnosed in 100% of cases.